Career choices, determinants, and need for medical career introduction among medical students - Syakurah, Rizma Adlia; Prabandari, Yayi Suryo; Widyandana, .; Kumara, Amitya (International Journal of Research in Medical Sciences, 2017)
Background: Having a specific assessment on medical students’ career preferences, their determinants for choosing them, and finding whether a career intervention in introducing career choices is consider needed in students’ point of view is important to generate an effective and suitable intervention for medical students, and can give appropriate support to the students. This study aimed to discover medical students’ career choices and their reasons for choosing those careers to find out their preferences. This study will also try to find their need of medical career intervention. Methods: The study conducted in cross sectional approach, und self-administered questionnaires was used to obtain the data. Results: Among 269 students, specialist is still considered as the most chosen career preference (75%) on students first, second and third choices. Followed by general practitioner, and hospital management. There was 7,8% of undecided students, and more that 75% students don’t have second and/or third career alternatives. Determinants of career choices with most votes are personal interest, social factors and experiences, with 35% of the students claiming not to know their reason for choosing their career preferences. Almost all the students agreed on wanting some activities to expose themselves to career choices, and they choose their first year, followed by third year and clerkship year as their preferred time to do the activities. Conclusions: Specialist is still the most sought out medical career, with personal interest and social factors as their main determinants. Career choices are needed to be introduce to students so they can have more options to choose from, and start to explore their career early.